The Effectiveness of Periodic Cardiovascular Screening in Preventing Sudden Cardiac Death in Young Athletes - Gólcz, Adrian; Szaryński, Mikołaj; Sikorski, Adam; Kadłubowska, Karolina; Chojnowska, Natalia; Rytel, Jan; Jakubowska, Paulina; Jakubowska, Martyna; Bursztyn, Michał; Bursztyn, Tomasz; et al. (Quality in Sport, 2025)
Sudden cardiac death (SCD) in young athletes, although rare, remains a major concern in sports cardiology due to its unpredictable occurrence in asymptomatic individuals. This review summarizes current evidence on the effectiveness of periodic cardiological assessment, including pre-participation screening (PPS), in preventing SCD among young athletes. The annual incidence is estimated at 1–3 cases per 100,000 athletes, higher than in non-athletic populations. In athletes under 35 years, hereditary and congenital cardiac disorders such as hypertrophic cardiomyopathy (HCM), arrhythmogenic right ventricular cardiomyopathy (ARVC), and channelopathies predominate, while in those over 35 years, atherosclerotic coronary artery disease is the main cause. Standard PPS protocols include medical and family history, physical examination, and a resting 12-lead electrocardiogram (ECG), with some programs incorporating exercise stress testing (EST) or advanced imaging. Evidence from long-term programs, particularly in Italy, shows that ECG-based screening can identify potentially life-threatening cardiac conditions and may reduce SCD incidence. However, high false-positive rates, economic costs, and logistical challenges limit its widespread implementation. The cost-effectiveness of PPS depends on disease prevalence, diagnostic accuracy, and healthcare capacity. Interpretation of findings requires specialized expertise to distinguish physiological adaptations from pathology. Although observational data are promising, randomized controlled evidence confirming reduced mortality is lacking. PPS programs should therefore be adapted to local healthcare systems, resources, and epidemiological profiles, while emerging technologies such as mobile cardiac monitoring and artificial intelligence may improve the precision and accessibility of future SCD prevention strategies.